Data on sulforaphane treatment mediated suppression of autoreactive, inflammatory M1 macrophages - Sanjima Pal; V. Badireenath Konkimalla (Data in Brief, 2016)
Any chronic, inflammatory, autoimmune disease (e.g. arthritis) associated pathogenesis directs uncontrolled accumulation of both soluble forms of collagens in the synovial fluids and M1 macrophages around inflamed tissues. Despite of few studies demonstrating efficiency of Sulforaphane (SFN) in suppressing arthritis associated collagen restricted T cells or fibroblasts, its effects on macrophage polarity and plasticity are less understood. Recently, we reported regulation of phenotypic and functional switching by SFN in induced and spontaneously differentiating human monocytes [1]. Here, flow cytometry, western blot and ELISA derived data demonstrated that SFN inhibited in vitro inflammatory responses developed by soluble human collagens (I–IV) induced auto-reactive M1 type monocyte/macrophage model.